Situation Report: Poland, 19 May 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Warsaw Attitude Prior to Nixon Visit More on the Gerhard Murder Case Voivodship [Voivodeship] People's Council Chairman and Party First Secretaries: A New Alignment of Provincial Power Tandems